Chronic Multi-Electrode Electromyography in Snakes - Jensen, Grady W.; van der Smagt, Patrick; Luksch, Harald; Straka, Hans; Kohl, Tobias (Frontiers in Behavioral Neuroscience, 2022)
Knowledge about body motion kinematics and underlying muscle contraction dynamics usually derives from electromyographic (EMG) recordings. However, acquisition of such signals in snakes is challenging because electrodes either attached to or implanted beneath the skin may unintentionally be removed by force or friction caused from undulatory motion, thus severely impeding chronic EMG recordings. Here, we present a reliable method for stable subdermal implantation of up to eight bipolar electrodes directly above the target muscles. The mechanical stability of the inserted electrodes and the overnight coverage of the snake body with a ’sleeping bag’ ensured the recording of reliable and robust chronic EMG activity. The utility of the technique was verified by daily acquisition of high signal-to-noise activity from all target sites over four consecutive days during stimulus-evoked postural reactions. This chronic recording technique thus can improve acute experiments by enabling the collection of larger data sets from single individuals.